Cosmopolíticas Tuxá: conhecimentos, ritual e educação a partir da autodemarcação de Dzorobabé - Durazzo, Leandro Marques (2019)
The aim of this thesis is to understand some political processes and Indigenous ways of knowledge among Tuxá people, improved by their involvement with a territorial autodemarcação (autodemarcation) of Dzorobabé land. Accordingly to them, Dzorobabé is their ancestral territory, traditionally and historically related to their ancestors in the region of Submédio São Francisco river. At once auto-demarcation highlights both sociopolitical organization and the dwelling process of living in a strong cosmological place, where the ancestors – brabios, gentios, mestres encantados – are present. This re-dwelling offers different ways to engage with Tuxá’s ciência (science), i.e., their complex of ritual practices and knowledges that structures their worldview, besides their political and educational planning within Indigenous school education. By the means of an ethnography, the thesis aims to comprehend the correlation between different Tuxá political-ritual groups and their ways to engage with ciência in the context of Dzorobabé autodemarcation during its first six months (August 2017 to February 2018). Political arrangements – division of political groups of families which constitute the current Conselho Tuxá (Tuxá Council) – point to specifics ways of relating with territory, both in its tangible and intangible dimensions. They also highlight the multiplicity of political groups among Tuxá in Rodelas, which reorganize themselves around the project of auto-demarcation to occupy the territory and reach future access to resources – political representativity, access to the land etc. Furthermore, we describe a twofold process of re-dwelling Dzorobabé. First, the political negotiations aiming to divide particular areas of the autodemarcation site to different groups, as well as sharing the responsability for the common spaces. Second, the different ways of engaging with the cosmological force of Dzorobabé that varies accordingly to different political-ritual groups dwelling the territory – and handling with its ciência. Given these points, we also study two ways of Indigenous education benefited by their contact with ciência: on the one hand there is what we call a wilderness pedagogy, cosmopolitically and ritually related to enchanted beings and the knowledge that comes from them; on the other hand there is a circulation through pedagogic repertoires (both Indigenous and non-Indigenous), a movement done especially by Indigenous teachers in close relation to the knowledge coming from the ciência besides school context. Focusing on the strengthening of educational and political repertoires by resorting to the ciência, we are able to understand how a number of projects come to be outlined, as for example the current revitalization of an Indigenous idiom. This revitalization is based upon different sources, both the direct communication with brabios and mestres encantados – which is enhanced by their coevalness in Dzorobabé – and the resort to colonial period documents, for instance the bilingual Portuguese-Dzubukuá catechism. The latter is a Karirian language of MacroJê stock which was spoken by native peoples around the region. Besides the ancestral territory, then, we can find the notion of an ancestral language that allows us to follow a multiple path of Tuxá territoriality, involving land (for the auto-demarcation), knowledge (for the ritual practices and the ciência) and school education (for the perspectives of ethnic strengthening and language revitalization promoted by the current Dzubukuá project).